EPIDEMIOLOGICAL TRENDS AND TRANSMISSION ROUTES OF HIV INFECTION IN THE FERGANA REGION: A RETROSPECTIVE STUDY (2010–2024) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Background: HIV infection remains an important public health problem in Uzbekistan, particularly in regions with high population density and intensive migration. The Fergana region is one of the areas where the epidemiological situation of HIV requires continuous monitoring and analysis. Objective: The aim of this study was to analyze the epidemiological trends, geographical distribution, and transmission routes of HIV infection in the Fergana region during the period 2010–2024. Methods: A retrospective epidemiological study was conducted using official surveillance data from the regional HIV monitoring system. HIV incidence rates were calculated per 100,000 population. District-level distribution, modes of transmission, and demographic characteristics of people living with HIV were analyzed using descriptive epidemiological methods.